A study on the effect of zinc oxide and zinc peroxide nanoparticles to enhance angiogenesis-pro-angiogenic grafts for tissue regeneration applications. (15th October 2017) - Ahtzaz, Samreen; Nasir, Muhammad; Shahzadi, Lubna; Amir, Walija; Anjum, Aneeq; Arshad, Rida; Iqbal, Farasat; Chaudhry, Aqif Anwar; Yar, Muhammad; Rehman, Ihtesham ur
Abstract: Angiogenesis is a process of formation of new small blood vessels from existing vessels and is very critical for proper and rapid tissue healing. As reactive oxygen species (ROS) are known for their ability to promote angiogenesis, in this study zinc oxide (ZnO) and zinc peroxide (ZnO2 ) nano-particles (NP's) encapsulated chitosan (CS) and cellulose based hydrogels were synthesized. ZnO2 is comparatively stronger oxidizing agent as compared to ZnO, therefore, in this study it was hypothesized that ZnO2 would deliver better angiogenic potential than ZnO. Three types of hydrogels were prepared; control hydrogel (without nano-particles), hydrogel having ZnO NP's and hydrogel having ZnO2 NP's. The hydrogels were characterized by scanning electron microscopy (SEM) for structural morphology, Fourier transform infrared spectroscopy (FTIR) for chemical functional groups analyses and X-ray Diffraction (XRD) to investigate the crystalline or amorphous structure of NP's. The solution absorption capacity was tested in PBS and degradation was investigated in PBS, PBS/H2 O2 and PBS/lysozyme solutions. The angiogenic behavior of these materials was studied in chorioallantoic membrane (CAM) assay and ZnO2 based material showed significant higher angiogenesis. Graphical abstract: Highlights: Crosslinking of chitosan and cellulose was performed using triethyl orthoformate. Zinc oxide and zinc peroxide nanoparticles were embedded into crosslinked polymeric matrix. Nanoparticles loaded hydrogels were subjected to chorioallantoic membrane assay to investigate their angiogenic potential. Zinc peroxide exhibited better angiogenic activity due to comparatively more onsite production of hydrogen peroxide.